Upaya Meningkatkan Disiplin Guru TK Melalui Sistem Reward and Punishment - Sabaruddin Sabaruddin (JURNAL GLOBAL EDUKASI, 2022)
Abstract: This study aims to determine the improvement of teacher discipline by providing teachers with a reward and punishment system. The subjects of this study were kindergarten teachers in Langkat district, totaling 20 teachers. The results of the research in the first cycle were 75% of teachers were able to apply the discipline of their arrival in every learning activity. The results of the research in the second cycle increased to 90% of teachers who were able to discipline the arrival time in each activity. In the first cycle there are 60% of teachers who complete the administration of learning preparation in their class, while in the second cycle it increases to 80%. Then in the first cycle there were 50% of the teachers did not reach the minimum curriculum target and in the second cycle it decreased to 20% did not reach the curriculum target. From this it can be concluded that teacher awareness in time discipline can improve student learning outcomes, as seen in the results of the research cycle I to cycle II, teacher performance and student learning outcomes have increased significantly. Keywords: discipline; punishment; reward  Abstrak: Penelitian ini bertujuan untuk mengetahui peningkatan disiplin guru dengan memberikan guru sistem reward dan punisment. Subjek penelitian ini adalah guru-guru TK di kabupaten Langkat yang berjumlah 20 orang guru. Hasil penelitian pada siklus I terdapat 75% guru mampu menerapkan disiplin kedatangannya di setiap kegiatan pembelajaran. Hasil penelitian pada siklus II meningkat menjadi 90% guru mampu melakukan disiplin waktu kedatangan di setiap kegiatan. Pada siklus I terdapat 60% guru yang lengkap administrasi persiapan pembelajaran di kelasnya, sedangkan pada siklus II meningkat menjadi 80%. Kemudian pada siklus I terdapat 50% guru tidak mencapai target kurikulum minimal dan pada siklus II menurun menadi 20% tidak mencapai target kurikulum. Dari hal ini dapat disimpulkan bahwa kesadaran guru dalam disiplin waktu dapat meningkatkan hasil belajar siswa, terlihat pada hasil penelitian siklus I sampai dengan siklus II, kinerja guru dan hasil belajar siswa mengalami peningkatan signifikan. Kata Kunci: disiplin; punishment; reward